The role of complement in nonalcoholic fatty liver disease - Guo, Zhenya; Fan, Xiude; Yao, Jianni; Tomlinson, Stephen; Yuan, Guandou; He, Songqing (Frontiers in Immunology, 2022)
Nonalcoholic fatty liver disease (NAFLD) has become a leading cause of chronic liver diseases globally. NAFLD includes a range of hepatic manifestations, starting with liver steatosis and potentially evolving towards non-alcoholic steatohepatitis, cirrhosis or even hepatocellular carcinoma. Although the pathogenesis of NAFLD is incompletely understood, insulin resistance and lipid metabolism disorder are implicated. The complement system is an essential part of the immune system, but it is also involved in lipid metabolism. In particular, activation of the alternative complement pathway and the production of complement activation products such as C3a, C3adesArg (acylation stimulating protein or ASP) and C5a, are strongly associated with insulin resistance, lipid metabolism disorder, and hepatic inflammation. In this review, we briefly summarize research on the role of the complement system in NAFLD, aiming to provide a basis for the development of novel therapeutic strategies for NAFLD.